Nerve ultrasound findings in neuropathy associated with anti‐myelin‐associated glycoprotein antibodies. (1st September 2014) - Lucchetta, M.; Padua, L.; Granata, G.; Luigetti, M.; Campagnolo, M.; Dalla Torre, C.; Coraci, D.; Sabatelli, M.; Briani, C.
<x xml:space="preserve">Abstract</x> Background and purpose No systematic nerve ultrasound (US) studies on patients with neuropathy and anti‐myelin‐associated glycoprotein (anti‐MAG) antibodies are available. Patients and methods Twenty‐eight patients (18 men, 10 women, mean age 69.2 ± 10.9 years; mean disease duration 6.9 years) with anti‐MAG neuropathy underwent nerve US. Echotexture, nerve cross‐sectional area (CSA) and intra‐nerve and inter‐nerve CSA variability were assessed. The frequency (number of nerves with enlarged CSA, 'enlarged nerves sum score') and distribution (proximal versus distal, arms versus legs, symmetry) of US abnormalities were considered. Controls included two groups: four patients with immunoglobulin M (IgM) paraproteinaemic neuropathy without anti‐MAG antibodies and five with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) associated with IgM paraprotein. Results In all, 26/28 patients had increased CSA (23 with at least one nerve outside entrapment sites). Intra‐nerve CSA variability was abnormal in 21/28 patients (in 14 for increased nerve CSA outside entrapment sites). Inter‐nerve CSA variability was abnormal in 16 patients (of whom half for CSA increase out of entrapment sites). The enlarged nerves sum score in anti‐MAG neuropathy patients was greater than in MAG‐negative paraproteinaemic neuropathies and lower than in CIDP. Intra‐nerve variability appeared instead similar in anti‐MAG and controls. No correlation was found between US findings and Inflammatory Neuropathy Cause and Treatment Group (INCAT) disability score or disease duration. Discussion Amongst the different measures to assess the US pattern (symmetry/asymmetry, proximal/distal distribution and sum score), the enlarged nerves sum score was the most useful for differentiating the three groups of patients with demyelinating neuropathies and may contribute to diagnosis in a typical cases.